Reproductive biology and feeding habits of the common dolphinfish Coryphaena hippurus (Linnaeus, 1758) off Saurashtra coast, India - Saroj, Jyoti; Koya, K. Mohammed; Mathew, K. L.; Tehseen, Panja (Indian Journal of Fisheries, 2018)
The present study analysed reproductive biology and feeding habits of the common dolphinfish Corphaena hippurus, along the Saurashtra coast of India. The study is based on an investigation of 295 specimens caught using drift gillnet at Veraval. The samples were collected on a monthly basis between March 2015 and February 2016. The sex ratio was 1:1.75 with a significant dominance of females in the population. The size at maturity for females was 593 mm FL (fork length). Absolute fecundity of the individuals ranged from 1,07,813 to 15,50,400 having ova diameter range of 0.3-1.96 mm. C. hippurus spawned throughout the year with its reproductive activity peaking in April and December. Thus the dolphin fish has an extended spawning season; during which it laid eggs almost continuously. A total of 128 stomachs of C. hippurus, whose fork length FL ranged from 380 to 1250 mm were examined during the one year period of this study. Tunas were found to be the common dietary component of the dolphinfish.